Modulation of Aleurone Peroxidases in Kernels of Insect-Resistant Maize (Zea mays L.; Pob84-C3R) After Mechanical and Insect Damage - López-Castillo, L. Margarita; González-Leyzaola, Alán; Diaz-Flores-Rivera, M. Fernanda; Winkler, Robert; Wielsch, Natalie; García-Lara, Silverio (Frontiers in Plant Science, 2020)
Peroxidases (PODs) have many biological functions during the plant life cycle. In maize kernels, endosperm PODs have been identified as biochemical contributors to resistance against Sitophilus zeamais, but their identities have not been determined. In this study, we identified these PODs and determined whether their contributions are basal or inducible. Semi-purification and LC-MS/MS analyses showed that the protein ZmPrx35 is the predominant soluble endosperm POD from Pob84-C3R maize. Subsequent time-course analyses after mechanical damage showed that POD activity is regulated in a fluctuating kinetics pattern and that zmprx35 mRNA expression levels reflected this pattern. After 48 h of infestation with S. zeamais or Prostephanus truncatus, soluble endosperm POD activities were 1.38- or 0.85-fold, respectively. Under the same conditions, zmprx35 expression was induced 1.61-fold (S. zeamais infestation) and 1.17-fold (P. truncatus infestation). These findings suggest that ZmPrx35 may contribute to the protective responses of aleurone cells against wounding and pest attacks, which could be enhanced/repressed by insect factors. Our data also provide evidence that the mechanisms of resistance towards the insect pests S. zeamais and P. truncatus are independent.